2007
DOI: 10.1007/s10749-007-0056-6
|View full text |Cite
|
Sign up to set email alerts
|

Internal-corrosion inhibitors for pipelines carrying deaerated heating water

Abstract: The effect of internal-corrosion inhibitors on heating-system pipelines is investigated. Tests were conducted on a testing device for polarization measurements under conditions corresponding to the Rostov Heat-Supply System. The concentration of OEDP-zinc, which provides a high degree of protection from general corrosion, is determined. The reagent has been successfully incorporated into the Rostov No. 2 TPP.According to [1], more than 220,000 km of water-heating grids, which operate primarily during the winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…These data have been confirmed at VTI under industrial conditions in Rostov-on-Don [6]. These experiments showed that the major antiscaling phosphonates (IOMS, OEDP, PAF-13A) also inhibit corrosion in deaerated water, but to a lesser extent than OEDP-Zn.…”
Section: Install Corrosion Indicatorssupporting
confidence: 59%
“…These data have been confirmed at VTI under industrial conditions in Rostov-on-Don [6]. These experiments showed that the major antiscaling phosphonates (IOMS, OEDP, PAF-13A) also inhibit corrosion in deaerated water, but to a lesser extent than OEDP-Zn.…”
Section: Install Corrosion Indicatorssupporting
confidence: 59%